Efficacy of sivelestat in alleviating postoperative pulmonary injury in patients with acute aortic dissection undergoing total arch replacement: a retrospective cohort study - Zhiyan Mai; Xudong Liu; Weixun Duan; Chen Yang; Yenong Zhou; Tao Chen; Zheng Su; Yang Yang; Jincheng Liu; Zhenxiao Jin (BMC Cardiovascular Disorders)
Abstract Objective Sivelestat may reduce postoperative pulmonary injury after total arch replacement (TAR). This study aimed to evaluate whether the preoperative PaO2/FiO2 (P/F) ratio affects the efficacy of sivelestat in reducing postoperative pulmonary injury in patients with acute aortic dissection (AAD) who underwent TAR using deep hypothermic circulatory arrest (DHCA). Methods Data of patients with AAD who underwent TAR using DHCA in a tertiary hospital between February 1, 2022, and December 30, 2022, were retrospectively reviewed. The patients were divided into the sivelestat and control groups. Three subgroup analyses were performed based on the postoperative P/F ratio. The primary clinical outcomes were assessed to determine the efficacy and safety of sivelestat in managing postoperative pulmonary dysfunction in patients undergoing cardiopulmonary bypass. Results A total of 187 patients were included, with 95 in the sivelestat group and 92 in the control group. No significant differences were found in the clinical variables between the two groups (all P > 0.05), except for some improvements in the inflammatory biomarker levels (including white blood cell count, neutrophil count, and C-reactive protein). Subgroup analysis revealed that sivelestat treatment significantly increased the P/F ratio on the 4th day and 3rd day after TAR in patients with mild lung injury (P = 0.02) and moderate lung injury (P = 0.03), respectively. Additionally, sivelestat reduced the levels of several postoperative inflammatory biomarkers in both subgroups. Conclusions Among patients with AAD with mild or moderate preoperative lung injury, defined by a low P/F ratio, sivelestat significantly improved the postoperative P/F ratio and attenuated inflammatory responses after TAR. These findings suggest an important avenue for further research.